EMPATHY OF SCHOOL COUNSELLOR IN SUPPORTING THE CAREER DECISION-MAKING PROCESS OF JUNIOR HIGH SCHOOL STUDENTS - Taufik Agung Pranowo; Arip Febrianto (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
This research aims to explore the role of school counselor empathy in supporting the career decision making process of Madrasah Tsanawiyahstudents. The research method used is a qualitative method. Data collection methods use in-depth interviews with school counselor, observation, and document analysis. The targets of this research are school counselor at Madrasah Tsanawiyah, Magelang Regency, Central Java Province. Data analysis in this research is 1) data collection, 2) data reduction, 3) data presentation, and 4) drawing conclusions. Test the validity of the data using Triangulation Technique. The research results show that school counselor Islamic Junior High Schools in Magelang Regency apply empathy effectively to build strong relationships with students, help them identify interests and potential, and provide relevant information regarding various career paths. The discussion highlighted the importance of empathy as the main key in guiding students to face future challenges and threats. In conclusion, the empathy of the school counselor at Madrasah Tsnawiyah Magelang Regency supports the students being guided to make further career decisions.